Venous thromboembolism in medical patients during hospitalisation and 3 months after hospitalisation: a prospective observational study. Issue 8 (3rd August 2016) - Khalafallah, Alhossain A; Kirkby, Brooke E; Wong, Sophia; Foong, Yi Chao; Ranjan, Nishant; Luttrell, James; Mathew, Ronnie; Chilvers, Charles M; Mauldon, Emily; Sharp, Colin; Hannan, Terry
Abstract : Objectives: This study was conducted to assess the incidence and risk factors for venous thromboembolism (VTE) in a cohort of medical patients both during the period of hospitalisation and following discharge. Design: This was a prospective observational study to document the risk profile and incidence of VTE posthospitalisation among all medical patients admitted to our institution during the trial period. Settings: Primary healthcare. Single tertiary referral centre, Tasmania, Australia. Participants: A total of 986 patients admitted to the medical ward between January 2012 and September 2012 were included in the study with male to female ratio of 497:489. The mean age of patients was 68 years (range 17–112, SD 16). Results: Overall, 54/986 patients (5.5%) had a VTE during the study period. Of these, 40/54 (74.1%) occurred during hospitalisation and 14/54 (25.9%) occurred following discharge. VTE risk factors revealed in multivariate analysis to be associated with a previous diagnosis of VTE (p<0.001, OR=6.63, 95% CI 3.3 to 13.36), the occurrence of surgery within the past 30 days (p<0.001, OR=2.52, 95% CI 1.33 to 4.79) and an admission diagnosis of pulmonary disease (p<0.01, OR 3.61, 95% CI 1.49 to 8.76). Mobility within 24 hours of admission was not associated with an increased risk. There was risk of VTE when the length of stay prolonged (p=0.046, OR=1.01, 95% CI 1.00 to 1.03), however it was not sustained with multivariate modelling. VTE-specific prophylaxis was used in 53% of the studied patients. Anticoagulation including antiplatelet agents were administered in 63% of patients who developed VTE. Conclusions: This prospective observational study found that 5.5% of the studied patients developed VTE. Among those, 25.9% (14/54) of patients had a detected VTE posthospitalisation with this risk being increased if there was a history of VTE, recent surgery and pulmonary conditions. Thromboprophylaxis may be worth considering in these cohorts. Further study to confirm these findings are warranted. Trial registration number: ACTRN12611001255976.